2016
DOI: 10.1007/s10021-016-0002-2
|View full text |Cite
|
Sign up to set email alerts
|

From Ethnobiology to Ecotoxicology: Fishers’ Knowledge on Trophic Levels as Indicator of Bioaccumulation in Tropical Marine and Freshwater Fishes

Abstract: Information on fish trophic levels is important to assess fishing impacts and to better understand the bioaccumulation of pollutants within aquatic food chains. The local ecological knowledge held by small-scale fishers can fill knowledge gaps in fish trophic ecology. We estimated the trophic levels of 69 tropical and subtropical fish species (33 coastal and 36 freshwater species) using data on fish diets from the literature and obtained from interviews with Brazilian fishers. The fish trophic levels estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 54 publications
7
23
0
2
Order By: Relevance
“…However, we emphasize that since the categorization as "positive," "neutral," or "negative" was made a posteriori by the authors, these results reveal a broad and simplified view of what is considered as a perception of improvement (i.e., positive) or loss (i.e., negative) in the environment. Similar observations are reported by Silvano and Begossi [22], who found that although fishermen knew about mercury contamination in fishery resources, they continued to consume this resource. As well as some residents noticing negative changes in the environment due to mining, 85% of residents said they know about the contamination of the mined areas; however, they still collect and use plant species from these areas.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, we emphasize that since the categorization as "positive," "neutral," or "negative" was made a posteriori by the authors, these results reveal a broad and simplified view of what is considered as a perception of improvement (i.e., positive) or loss (i.e., negative) in the environment. Similar observations are reported by Silvano and Begossi [22], who found that although fishermen knew about mercury contamination in fishery resources, they continued to consume this resource. As well as some residents noticing negative changes in the environment due to mining, 85% of residents said they know about the contamination of the mined areas; however, they still collect and use plant species from these areas.…”
Section: Discussionsupporting
confidence: 88%
“…In Brazil, contamination of soil, plant, and fishery resources also poses a health risk to local communities [21,22]. Coal mining in Brazil began in the late nineteenth century, and today, practically all coal produced in Brazil is mined in the southern area [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that information is lacking for important target species and consumed species from both the coastal and continental waters of Brazil [9,10]. Another area in which the fishers can help is the monitoring of contaminants: as the study by Silvano and Begossi [44] shows, observations of bioaccumulation, such as the mercury content in fish muscle, can be made by fishers and can be very valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Os bioensaios de toxicidade, em sua maioria, são realizados em regiões temperadas, utilizando-se espécies e condições experimentais representativas dessas regiões, resultando incongruências nos resultados, quando comparados às regiões tropicais. Desta forma, muitos autores recomendam a utilização de espécies nativas em testes ecotoxicológicos sob condições representativas de regiões tropicais (BUCH et al, 2017;GHOSE et al, 2014;HOWE;REICHELT-BRUSHETT;CLARK, 2014;MANSANO et al, 2018;ROCHA et al, 2018b;SILVANO;BEGOSSI, 2016 Além disso, conclui-se que os bioensaios ecotoxicológicos são uma importante ferramenta na complementação das análises de monitoramento de reatores, e que os invertebrados Chironomus sancticaroli, Allonais inaequalis e Daphnia magna apresentam sensibilidade aguda e crônica ao LAS padrão e às amostras do reator, e podem ser recomendados como organismos-teste em bioensaios de no monitoramento.…”
Section: Considerações Finaisunclassified